2022
DOI: 10.1158/2767-9764.crc-21-0090
|View full text |Cite
|
Sign up to set email alerts
|

Brain Neural Progenitors are New Predictive Biomarkers for Breast Cancer Hormonotherapy

Abstract: Heterogeneity of the tumor microenvironment (TME) is one of the major causes of treatment resistance in breast cancer. Among TME components, nervous system role in clinical outcome has been underestimated. Identifying neuronal signatures associated with treatment response will help to characterize neuronal influence on tumor progression and identify new treatment targets. The search for hormonotherapy-predictive biomarkers was implemented by supervised machine learning (ML) analysis on merged transcriptomics d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Brain neural progenitor presence and perineural invasion were found to be nervous system-related mechanisms that were positively associated with NervSign97 and a poor clinical prognosis in patients receiving hormone therapy, according to pathway enrichment scores and deconvolution analysis. Further investigation into the role of neuronal components in tumor progression is warranted in light of the identification of two nervous-system-related signatures via transcriptomic profiling that were verified in clinical samples as hormonotherapy-predictive signatures [46]. Such a study provided two hormonotherapy-predictive and prognostic signatures related to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain neural progenitor presence and perineural invasion were found to be nervous system-related mechanisms that were positively associated with NervSign97 and a poor clinical prognosis in patients receiving hormone therapy, according to pathway enrichment scores and deconvolution analysis. Further investigation into the role of neuronal components in tumor progression is warranted in light of the identification of two nervous-system-related signatures via transcriptomic profiling that were verified in clinical samples as hormonotherapy-predictive signatures [46]. Such a study provided two hormonotherapy-predictive and prognostic signatures related to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Authors [46] presented prognostic and predictive signatures pertaining to the neurological system. Such a work indicated that through a better understanding of the molecular processes behind these genes, new prognostic biomarkers for prognosis prediction or chemotherapy sensitivity could be developed.…”
Section: Discussionmentioning
confidence: 99%